2021
DOI: 10.1016/j.jinf.2021.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Structural dynamics of SARS-CoV-2 variants: A health monitoring strategy for anticipating Covid-19 outbreaks

Abstract: Objectives The Covid-19 pandemic has been marked by sudden outbreaks of SARS-CoV-2 variants harboring mutations in both the N-terminal (NTD) and receptor binding (RBD) domains of the spike protein. The goal of this study was to predict the transmissibility of SARS-CoV-2 variants from genomic sequence data. Methods We used a target-based molecular modeling strategy combined with surface potential analysis of the NTD and RBD. Results We observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
138
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 62 publications
(144 citation statements)
references
References 53 publications
6
138
0
Order By: Relevance
“…This is likely due to closer positioning and flexibility of RBD residues such as Q493. Recent reports have suggested that the E484K mutation may enhance ACE2 binding via increasing electrostatic complementarity between ACE2 and the RBD (Dejnirattisai et al, 2021;Fantini et al, 2021), and the structures reported here are consistent with that hypothesis. The combination of the L452R mutation with either Beta or Gamma variant RBD mutations (D614G + N501Y + E484K + K417N/T) did not further increase ACE2 affinity.…”
Section: Discussionsupporting
confidence: 90%
“…This is likely due to closer positioning and flexibility of RBD residues such as Q493. Recent reports have suggested that the E484K mutation may enhance ACE2 binding via increasing electrostatic complementarity between ACE2 and the RBD (Dejnirattisai et al, 2021;Fantini et al, 2021), and the structures reported here are consistent with that hypothesis. The combination of the L452R mutation with either Beta or Gamma variant RBD mutations (D614G + N501Y + E484K + K417N/T) did not further increase ACE2 affinity.…”
Section: Discussionsupporting
confidence: 90%
“…Such a charge distribution promotes the spike corona stability and enhances the virion attachment to receptors and surfaces, mostly negatively charged, 20 eg, gangliosides-rich lipid rafts. 21 …”
Section: Discussionmentioning
confidence: 99%
“…The antibody studied is 1054 (pdb file #7LAB) which has been isolated from a symptomatic Covid-19 patient 1 . Molecular modelling simulations were performed as previously described 2 . Two currently circulating Delta variants were investigated, with the following mutational patterns in the NTD : - G142D/E154K (B.1.617.1) - T19R/E156G/del157/del158/A222V (B.1.617.2) …”
mentioning
confidence: 99%
“…Overall, the energy of interaction of the NTD-raft complex was raised from -399 kJ.mol −1 in absence of the antibody to -457 kJ.mol −1 with the antibody. By clamping the NTD and the lipid raft, the antibody reinforces the attachment of the spike protein to the cell surface and thus facilitates the conformational change of the RBD which is the next step of the virus infection process 2 .
Figure 1 Infection enhancing antibodies recognize the NTD of Delta variants.
…”
mentioning
confidence: 99%